The Centaur Types. - Rogers, Bruce (Purdue University Press, 2018)
In 1948, the world-renowned book designer Bruce Rogers wrote a brief text that documented and illustrated his creation of the Centaur typeface several decades earlier: The Centaur Types. The book was privately printed by Rogers himself under the name of his design studio, October House. This limited edition of the book was transferred to the Purdue University Libraries at the time of his death along with his other papers and books. Over the years remaining stock of the original private printing has found its home in the Special Collections of the Libraries, and although known as something of a collector's item by those who are aware of the few copies in circulation, it is here available to the general market for the first time in both paperback and digital versions. The Centaur Types is a fascinating book for several reasons: in the designer's own words, we learn of the evolution of the typeface and of his interest in the art and craft of creating type; it demonstrates different and comparable typefaces, and gives examples of Centaur from six to seventy-two point; and it stands as a fitting example of fine bookmaking from one of the master book designers of the twentieth century.